Research on Multi-Scenario Distributed Wind and Photovoltaic Power Accommodation Capacity of Distribution Network Based on Time Series Production Simulation. Issue 1 (August 2020) - Wu, Jun; Ma, Shiyi; Duan, Cong
Abstract: With the large-scale access of distributed new energy into the distribution network, the evaluation on the accommodation capacity of distributed new energy in the distribution network has important guiding significance for the scientific planning of distributed generation and grid connection. Considering the parked and regionalized development trend of distributed power generation mode, this paper proposes a method for evaluating the distributed wind and photovoltaic power accommodation capacity of regional distribution networks based on time series production simulation from the perspective of practical applications. Based on the timing difference and complementarity of the load characteristics of substations on the distribution network side, we conducted an evaluation on the distributed wind and photovoltaic power accommodation capacity of the regional distribution network, and through taking the flexible operation mode of the distribution network side into consideration, realized the mutual assistance from time domain and space dimension of distributed new energy consumption and carrying capacity of various substations. Through establishing a mathematical model for the consumption and carrying capacity analysis in the multi-scenario modes such as local node consumption, local station consumption and allowing certain percentage of abandoned electricity, we came out the scale of the maximum consumption of distributed new energy in different scenarios as well as the overall grid connection layout scheme. In the end, we used such evaluation method to conduct an empirical analysis on the distribution network in certain region, verified the correctness and effectiveness of the model, and provided theoretical supports for guiding the regional distributed new energy overall planning and scientific grid connection.